Does over a century of aerobic phage work provide a solid framework for the study of phages in the gut?. (April 2021) - Shareefdeen, Hiba; Hynes, Alexander P.
Abstract: Bacterial viruses (bacteriophages, phages) of the gut have increasingly become a focus in microbiome studies, with an understanding that they are likely key players in health and disease. However, characterization of the virome remains largely based on bioinformatic approaches, with the impact of these viromes inferred based on a century of knowledge from aerobic phage work. Studying the phages infecting anaerobes is difficult, as they are often technically demanding to isolate and propagate. In this review, we primarily discuss the phages infecting three well-studied anaerobes in the gut: Bifidobacterium, Clostridia and Bacteroides, with a particular focus on the challenges in isolating and characterizing these phages. We contrast the lessons learned from these to other anaerobic work on phages infecting facultative anaerobes of the gut: Enterococcus and Lactobacillus. Phages from the gut do appear to adhere to the lessons learned from aerobic work, but the additional challenges of working on them has required ingenious new approaches to enable their study. This, in turn, has uncovered remarkable biology likely underpinning phage-host relationships in many stable environments. Highlights: Phages of anaerobes are challenging to isolate and characterize. Ingenious approaches beyond the plaque assay have been required for phage discovery. These approaches have identified abundant phages with life cycles that seem suited to stable long-term relationships with their hosts. There is no reason to assume these are unique to anoxic environments, should these techniques be applied elsewhere.